The potential effects of introducing microneedle patch vaccines into routine vaccine supply chains. Issue 4 (21st January 2019) - Wedlock, Patrick T.; Mitgang, Elizabeth A.; Elsheikh, Fayad; Leonard, Jim; Bakal, Jenn; Welling, Joel; Crawford, Jessica; Assy, Emmanuelle; Magadzire, Bvudzai P.; Bechtel, Ruth; DePasse, Jay V.; Siegmund, Sheryl S.; et al.
Abstract: Background: Microneedle patch (MNP) technology is designed to simplify the process of vaccine administration; however, depending on its characteristics, MNP technology may provide additional benefits beyond the point-of-use, particularly for vaccine supply chains. Methods: Using the HERMES modeling software, we examined replacing four routine vaccines – Measles-containing vaccine (MCV), Tetanus toxoid (TT), Rotavirus (Rota) and Pentavalent (Penta) – with MNP versions in the routine vaccine supply chains of Benin, Bihar (India), and Mozambique. Results: Replacing MCV with an MNP (5 cm 3 -per-dose, 2-month thermostability, current single-dose price-per-dose) improved MCV availability by 13%, 1% and 6% in Benin, Bihar and Mozambique, respectively, and total vaccine availability by 1% in Benin and Mozambique, while increasing the total cost per dose administered by $0.07 in Benin, $0.56 in Bihar and $0.11 in Mozambique. Replacing TT with an MNP improved TT and total vaccine availability (3% and <1%) in Mozambique only, when the patch was 5 cm 3 and 2-months thermostable but increased total cost per dose administered by $0.14. Replacing Rota with an MNP (at 5–15 cm 3 -per-dose, 1–2 month thermostable) improved Rota and total vaccine availability, but only improved Rota vaccine availability in Bihar (at 5 cm 3, 1–2 months thermostable), while decreasing total vaccine availability by 1%. Finally, replacing Penta with an MNP (at 5 cm 3, 2-months thermostable) improved Penta vaccine availability by 1–8% and total availability by <1–9%. Conclusions: An MNP for MCV, TT, Rota, or Penta would need to have a smaller or equal volume-per-dose than existing vaccine formulations and be able to be stored outside the cold chain for a continuous period of at least two months to provide additional benefits to all three supply chains under modeled conditions.